Related Factors with Self-Management Behaviors among Patients with Predialysis Chronic Kidney Disease: A Multicenter Study in Myanmar - Wint, Yoon Zarchi; Lininger, Jiraporn; Leelacharas, Sirirat (UI Scholars Hub, 2023)
Background: Self-management behavior is key to managing patients with predialysis chronic kidney disease (CKD) and is effective in slowing disease progression in impoverished Burmese patients with CKD. This study aimed to outline the association of personal and environmental factors with the self-management behaviors of people with predialysis CKD. Methods: Using convenience sampling, this cross-sectional study included 84 individuals with predialysis CKD from two private hospitals in Myanmar. The interviewer-administered questionnaire included demographic information, the Health Literacy Short Form-12, the CKD knowledge questionnaire, the self-efficacy questionnaire, the Multidimensional Scale of Perceived Social Support, and the self-management behavior questionnaire. This study analyzed the data using descriptive statistics, Pearson’s correlation coefficients, Spearman’s rho correlation, and Chi-square tests. Results: The results revealed that participants had moderate health literacy (26.12 ± 7.51), CKD knowledge (10.10 ± 3.76), and perceived self-efficacy levels (30.58 ± 10.28), a high social support level (67.33 ± 8.54), and a moderate self-management behavior level (74.20 ± 7.80). Health literacy (r = 0.40, p < 0.01), CKD knowledge (r = 0.62, p < 0.01), perceived self-efficacy (r = 0.62, p < 0.01), and social support (r = 0.44, p < 0.01) were related to self-management behaviors. Conclusions: The results indicated that enhanced health literacy, CKD knowledge, self-efficacy, and social support could support the self-management behaviors of individuals with predialysis CKD.